Boiling vapour-type fluids from the Nifonea vent field (New Hebrides Back-Arc, Vanuatu, SW Pacific): Geochemistry of an early-stage, post-eruptive hydrothermal system. (15th June 2017) - Schmidt, Katja; Garbe-Schönberg, Dieter; Hannington, Mark D.; Anderson, Melissa O.; Bühring, Benjamin; Haase, Karsten; Haruel, Christy; Lupton, John; Koschinsky, Andrea
Abstract: In 2013, high-temperature vent fluids were sampled in the Nifonea vent field. This field is located within the caldera of a large shield-type volcano of the Vate Trough, a young extensional rift in the New Hebrides back-arc. Hydrothermal venting occurs as clear and black smoker fluids with temperatures up to 368 °C, the hottest temperatures measured so far in the western Pacific. The physico-chemical conditions place the fluids within the two-phase field of NaCl–H2 O, and venting is dominated by vapour phase fluids with Cl concentrations as low as 25 mM. The fluid composition, which differs between the individual vent sites, is interpreted to reflect the specific geochemical fluid signature of a hydrothermal system in its initial, post-eruptive stage. The strong Cl depletion is accompanied by low alkali/Cl ratios compared to more evolved hydrothermal systems, and very high Fe/Cl ratios. The concentrations of REY (180 nM) and As (21 μM) in the most Cl-depleted fluid are among the highest reported so far for submarine hydrothermal fluids, whereas the inter-element REY fractionation is only minor. The fluid signature, which has been described here for the first time in a back-arc setting, is controlled by fast fluid passage through basaltic volcanic rocks, with extremely high water-rock ratios and only limited water-rock exchange, phase separation and segregation, and (at least) two-component fluid mixing. Metals and metalloids are unexpectedly mobile in the vapour phase fluids, and the strong enrichments of Fe, REY, and As highlight the metal transport capacity of low-salinity, low-density vapours at the specific physico-chemical conditions at Nifonea. One possible scenario is that the fluids boiled before the separated vapour phase continued to react with fresh glassy lavas. The mobilization of metals is likely to occur by leaching from fresh glass and grain boundaries and is supported by the high water/rock ratios. The enrichment of B and As is further controlled by their high volatility, whereas the strong enrichment of REY is also a consequence of the elevated concentrations in the host rocks. However, a direct contribution of metals such as As from magmatic degassing cannot be ruled out. The different fluid end-member composition of individual vent sites could be explained by mixing of vapour phase fluids with another fluid phase of different water/rock interaction history.